2001
DOI: 10.1095/biolreprod65.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gestational Deficiencies in Cloned Sheep Fetuses and Placentae1

Abstract: Sheep fetal development at 35 days of gestation was examined following natural mating, in vitro production (IVP) of fertilized embryos, or somatic cell nuclear transfer (NT). Five crossbred (Blackface x Black Welsh) and four purebred (Black Welsh) fetuses and their associated placentae produced by natural mating were morphologically normal and consistent with each other. From 10 ewes receiving 21 IVP embryos, 17 fetuses (81%) were recovered, and 15 of these (88%) were normal. The NT fetuses were derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
1
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 28 publications
7
125
1
8
Order By: Relevance
“…Most placentas from sheep at day 30 after scNT embryo transfer display avascularization and hypovascularization (De Sousa et al, 2001) effects that are also observed in our studies with pigs. To confirm the data, the level of angiogenic-related molecules such as VEGF, ANG-1 and -2, VEG-FRI, VEGF-RII, and TIE-2 mRNA was determined in control and scNT placentas by real-time RT-PCR (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Most placentas from sheep at day 30 after scNT embryo transfer display avascularization and hypovascularization (De Sousa et al, 2001) effects that are also observed in our studies with pigs. To confirm the data, the level of angiogenic-related molecules such as VEGF, ANG-1 and -2, VEG-FRI, VEGF-RII, and TIE-2 mRNA was determined in control and scNT placentas by real-time RT-PCR (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, multiple lines of experimental evidence have led to the conclusion that EET is the origin of the developmental pathologies in placentation of SCNTderived clones (17,(22)(23)(24)(25)(26). Therefore, study of the communication between cloned conceptuses and the endometrium should yield important insights into the mechanisms underlying average losses of ∌60% of cloned embryos before implantation and 80% of fetuses within the first trimester of gestation (27,28).…”
Section: Significancementioning
confidence: 99%
“…Initial studies had described only the placenta in those rare pregnancies that made it to term. In cattle and sheep, the term placenta in clones is characterised by a reduced number of cotyledons, hydroallantois and hypertrophy of remaining placentomes (Hill et al 1999;De Sousa et al 2001). Interestingly, the maternal caruncles are also underdeveloped, implying that primary fetoplacental defects indirectly affect the mother also (Hashizume et al 2002).…”
Section: Placental Mal-development In Cloned Animalsmentioning
confidence: 99%